A Method for 3D Immunostaining and Optical Imaging of the Mouse Brain Demonstrated in Neural Progenitor Cells - Gleave, Jacqueline A. (Public Library of Science, 2013)
It is important to understand changes in cell distribution that occur as a part of disease progression. This is typically achieved using standard sectioning and immunostaining, however, many structures and cell distribution patterns are not readily appreciated in two-dimensions, including the distribution of neural stem and progenitor cells in the mouse forebrain. Three-dimensional immunostaining in the mouse brain has been hampered by poor penetration. For this reason, we have developed a method that allows for entire hemispheres of the mouse brain to be stained using commercially available antibodies. Brains stained for glial fibrillary acidic protein, doublecortin and nestin were imaged in three-dimensions using optical projection tomography and serial two-photon tomography. This staining method is simple, using a combination of heat, time and specimen preparation procedures readily available, so that it can be easily implemented without the need for specialized equipment, making it accessible to most laboratories.